ELECTRICAL PROPERTIES OF (FeCoZr)x(Al2O3)(100-x) NANOCOMPOSITES PRODUCED BY SPUTTERING OF ARGON AND OXYGEN BEAM AS CAPACITOR SYSTEMS - Kierczyński, Konrad; Kołtunowicz, Tomasz (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2015)
The paper presents the results of measurements which determine the electrical properties of nanocomposites (FeCoZr)x(Al2O3)(100-x) which were produced using the ion-sputtering. In the research samples, which were made as capacitor measurement system, were used to reduce the impact of resistance of the sample. Temperature and frequency dependence on capacity, conductance, loss angle and phase angle were determined. Measurements were performed using alternating current at a frequency range from 42 Hz to 1 MHz at temperatures range from 77 K to 373 K.